Conventional and unconventional treatments for stress among methadone-maintained patients: treatment willingness and perceived efficacy. - Barry, Declan T; Beitel, Mark; Breuer, Timothy; Cutter, Christopher J; Savant, Jonathan; Schottenfeld, Richard S; Rounsaville, Bruce J (The American journal on addictions / American Academy of Psychiatrists in Alcoholism and Addictions, 2011)
We surveyed 150 methadone maintenance treatment (MMT) program patients about willingness to use, and perceived efficacy of, conventional and unconventional nonpharmacological stress-related treatments. Although levels of treatment willingness and perceived efficacy for both conventional and unconventional treatments were high, ratings for conventional interventions were, on average, significantly higher than those for unconventional ones. Dimensions of psychiatric distress-but not demographic or MMT characteristics-predicted treatment willingness for conventional therapies and treatment willingness and perceived efficacy for unconventional therapies. These findings are likely to have implications for resource and program planning in MMT programs.
Keywords: Adult; Attitude to Health; Complementary Therapies; Cross-Sectional Studies; Female; Humans; Male; Methadone; Middle Aged; Opiate Substitution Treatment; Opioid-Related Disorders; Patient Acceptance of Health Care; Psychotherapy; Stress, Psychological